A retrospective study detecting the neurovascular anatomical variations in the anterior palate observed on cone beam computed tomography images - Ashni Chatterjee; Ajay Bhoosreddy; Seema Bhoosreddy; Manjari Chaudhary; Akanksha Bhandari; Apurva Patil (Wolters Kluwer Medknow Publications, 2017)
Introduction: Premaxilla or the anterior maxilla is one of the most important sites for different surgical procedures, and any variations in the normal anatomic features can lead to misdiagnosis and altered treatment planning for a clinician. Hence, it is very necessary for the early detection and evaluation of the anatomical variations associated with anterior maxillary region, and the procedure becomes easy with the incorporation of the specific radiologic appliances such as cone beam computed tomography (CBCT). Materials and Methods: One hundred CBCT scans were collected retrospectively for examination of additional foramina and canals in the anterior palatal region, through CBCT images, describing location, and diameter. Results: The mean canal diameter was 1.4 mm, out of the 100 scans evaluated 11 scans were found in which additional foramina were detected and 9 scans wherein canalis sinosus was detected. The mean canal diameter was 1.4. Conclusion: Although there are variations in each patient, with the knowledge of the anatomic landmarks and with the use of advanced imaging techniques, the chances of error in diagnosis and treatment planning can be greatly reduced.